Exposure to crystalline silica, silicosis, and lung disease other than cancer in diatomaceous earth industry workers: a quantitative risk assessment. Issue 1 (1st January 2002) - Park, R; Rice, F; Stayner, L; Smith, R; Gilbert, S; Checkoway, H
Abstract : Objectives: To estimate excess lifetime risk of ( a ) mortality from lung disease other than cancer (LDOC), and, ( b ) onset of radiographic silicosis, arising from occupational exposure to respirable crystalline silica dust. Methods: Data from a cohort of California diatomaceous earth mining and processing workers exposed to crystalline silica dust (mainly as cristobalite) were reanalyzed with Poisson regression methods with internal and external adjustments for potential confounding by calendar time, age, smoking, Hispanic ethnicity, and time since first observation. Model fit was evaluated by comparing deviances and fitting cubic spline models. Lifetime risks of death from LDOC and radiographic silicosis were estimated up to age 85 with an actuarial approach accounting for competing causes of death. Results: For deaths due to LDOC, a linear relative rate model gave the best fit in Poisson regression analyses. At the mean cumulative exposure of LDOC cases to silica, after adjustment for smoking, the estimated rate ratio was 4.2 (p<0.0001); at the maximum cumulative exposure of cases, the rate ratio was 18.4. The excess lifetime risk for white men exposed to respirable cristobalite dust for 45 years at the current permissible exposure limit (PEL; about 0.05 mg/m 3 ) of the Occupational Safety and Health Administration was 54/1000 (95% confidence interval (95% CI) 17 to 150). For 70 incident cases of radiographic silicosis largely manifest before the end of employment, the best fit was also the linear relative rate model, predicting a rate ratio of 25.6 for silicosis at the mean cumulative exposure of the cases (p<0.0001). The excess lifetime risk for silicosis at the current PEL was 75/1000. Conclusion: Current occupational health standards for crystalline silica permit risks of lung disease other than cancer far in excess of what is usually considered acceptable by the Occupational Safety and Health Administration (a lifetime risk of less than one in a thousand deaths).